Analýza úrovně marketingového plánování v podnicích chemického průmyslu - Kohoutová, Martina; Lošťáková, Hana (Univerzita Pardubice, 1998)
This paper deals with marketing planning of enterprises and its strategic business units in present changing marketing environment. It summarises the results of research of content and methods of marketing planning in conditions of chemical industry.
Keywords: chemický průmysl; marketingové plánování; Analýza